Morusin Suppresses Pancreatic Cancer Cell Proliferation and Migration by Targeting SLC6A12 to Inhibit NF-κB and β-catenin Signaling Pathways - Yang, Wenyan; Zhu, Wei; Yao, Zhiyang; Wang, Zhao; Liu, Shengzhi; Guan, Xiaoqing; Qin, Jiang-Jiang (Recent Patents on Anti-Cancer Drug Discovery, 2025)
<span class=
Keywords: NF-κB